PaR (Plan-act-Review) Golf: Motor learning research and improving golf skills - Lee, T. D.; Schmidt, R. A. (International Journal of Golf Science, 2014)
In this paper we review the motor learning literature concerning the effects of conditions of practice and methods of providing augmented feedback on the acquisition of motor skills. Specific attention is provided to research that concerns the learning of golf skills. We interpret the results of this research with particular recommendations and implications for conducting golf practice. The term "PaR golf" refers to a recommendation that practice should emphasize the Planning and Review components of the golf swing during practice, and de-emphasize the importance of the repetitious act of executing golf swings. These recommendations are consistent with the principle that golf practice that best simulates play on the course will optimize learning.